2005
DOI: 10.1103/physrevb.72.224509
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous electron-phonon coupling probed on the surface of superconductorZrB12

Abstract: Magnetization measurements under hydrostatic pressure up to 10.5 kbar in zirconium dodecaboride ZrB12 superconductor (Tc ≃ 6.0 K at p = 0) were carried out. A negative pressure effect on Tc with dTc/dp = −0.0225(3) K/kbar was observed. The electron-phonon coupling constant λ el−ph decreases with increasing pressure with d ln λ el−ph /dp ≃ −0.20%/kbar. The magnetic field penetration depth λ was studied in the Meissner state and, therefore, probes only the surface of the sample. The absolute values of λ and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
5
29
0
2
Order By: Relevance
“…Note that the independence of the ratio 2∆(0)/k B T c of pressure was recently confirmed for RbOs 2 O 6 [13] and ZrB 12 [14] BCS superconductors. The resulting λ(0) vs. p dependence is shown in the inset of the Fig.…”
mentioning
confidence: 52%
“…Note that the independence of the ratio 2∆(0)/k B T c of pressure was recently confirmed for RbOs 2 O 6 [13] and ZrB 12 [14] BCS superconductors. The resulting λ(0) vs. p dependence is shown in the inset of the Fig.…”
mentioning
confidence: 52%
“…In the late 1960s, Matthias et al [2] found that ZrB 12 has the highest superconducting critical temperature (T c % 6 K) in several of metal dodecaborides (M = Sc, Y, Zr, La, Lu, and Th). In order to understand its superconducting behavior, this compound has been widely studied in virtue of recent progress in growing large high quality single crystals of dodecaborides [3][4][5][6][7][8]. It was previously considered that the superconductivity in ZrB 12 is directly connected with the vibrations of boron complexes [3].…”
Section: Introductionmentioning
confidence: 99%
“…33 For ZrB 12 , an electron-phonon coupling constant Х 1 was extracted in this way, in agreement with previous reports. [34][35][36] Figure 8 shows a comparison at low temperature of the low-frequency part of the reflectivity for the two compounds. The fits, including the contribution from the electron-phonon interaction as described above, are presented by a solid red line.…”
Section: ͑1͒mentioning
confidence: 99%